2022
DOI: 10.1002/joa3.12676
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the atrial wall thickness in normal/mild late‐gadolinium enhancement areas on atrial fibrillation rotors in persistent atrial fibrillation patients

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A computer modelling study [16] demonstrated that AF drivers drifted towards and anchored to the CT/PMs and the surrounding atrial wall in the RA due to a large source-to-sink mismatch. Interestingly, a recent clinical study indicated that AWT was thinner in LA AF drivers than in non-drivers (2.1 ± 0.2 mm versus 2.23 ± 0.3 mm, p < 0.05) in moderated gadolinium-enhanced areas [17]. Notably, their clinical MRI had a relatively low spatial resolution of approximately 1.3 mm which could explain the discrepancy in the LA AWT, compared with our high-resolution MRI results (4.2 ± 1.9 mm versus 4.5 ± 1.9 mm).…”
Section: Discussionmentioning
confidence: 99%
“…A computer modelling study [16] demonstrated that AF drivers drifted towards and anchored to the CT/PMs and the surrounding atrial wall in the RA due to a large source-to-sink mismatch. Interestingly, a recent clinical study indicated that AWT was thinner in LA AF drivers than in non-drivers (2.1 ± 0.2 mm versus 2.23 ± 0.3 mm, p < 0.05) in moderated gadolinium-enhanced areas [17]. Notably, their clinical MRI had a relatively low spatial resolution of approximately 1.3 mm which could explain the discrepancy in the LA AWT, compared with our high-resolution MRI results (4.2 ± 1.9 mm versus 4.5 ± 1.9 mm).…”
Section: Discussionmentioning
confidence: 99%